Caracterização do óleo de patauá e utilização para obtenção de um reagente coletor para a flotação de minério fosfático - Priscila Silva de Oliveira (2017)
As food demand increases and biofuel use expands, the world phosphate rock production substantially rises. The igneous and sedimentary phosphate rocks are the major economic viable source of phosphorous, which majorly undergo the flotation process to produce concentrates that will be an input for the fertilizer industry. In this process, fatty acids soaps derived from vegetable sources have been extensively used as collector reagents. Despite many fatty acids are available, the use of oleic acid and, in minor proportion, linoleic acid for this purpose is a consolidated practice, because unsaturated fatty acids present higher collect power than saturated ones. In this sense, this study aimed for evaluate the use of pataua (Oenocarpus bataua) vegetable oil, which is highly unsaturated, as an input for obtainment of an collector reagent for a phosphate ore from Itataia, Brazil. The reagent was obtained by means of hot saponification process, using sodium hydroxide and anhydrous ethanol solution, and under reflux. The investigation of the reagent applicability consisted in fundamental studies, such as microflotation, zeta potential and FTIR; and bench scale experiments. To correlate the vegetable oil and collector reagent properties, it was performed the characterization of both materials. The analyzed pataua vegetable oil presented a fatty acids composition consistent with the literature, but an uncommon free fatty acid index. Such high acidity is not harmful but potentially beneficial for its application as a flotation reagent, once this feature favored the saponification reaction and resulted in a collector reagent with a saponification degree close to 100%. The pataua oil composition rich in unsaturated fatty acids, especially oleic and linoleic acids, promoted selective apatite recovery during microflotation tests under lower collector concentrations. This result is due to the molecules tendency of reaching a lower packing degree, if compared to reagents composed of only one type of molecule (such as sodium oleate), which also reflects in the lower value of critical micelle concentration (CMC). The collector adsorption onto apatite surface was verified in every pH value analyzed, controlled by chemisorption and insoluble salts precipitation mechanisms, that caused a shift in the liquid surface charge modules towards more negative values. The adsorption of the collector was less significant onto calcite and quartz surfaces, evidenced by the FTIR spectra and small changes on potential zeta values. Thus, it is suggested the promising use of pataua oil for apatite flotation systems.